Pengaruh sedimen Das Sentani masuk ke Sungai Harapan Kabupten Jayapura - Iriani, Harbianti Rina Dwi; Musa, Ratna; Latief , Andi Amin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Sediment produced from the erosion process can come from various types of soil erosion such as surface erosion and river bank erosion. The sediment then settles in several locations, such as foothills, flood areas, waterways, rivers and reservoirs. The amount of sediment transported and deposited at a location can be measured based on a certain time period. An uncontrolled increase in sedimentation rates can cause various environmental problems, one of which is shallowing of rivers and reservoirs which has an impact on water holding capacity and increases the potential for flooding in the surrounding area. The aim of the research is to determine the potential erosion rate and potential sedimentation rate, as well as to find out the influence of sediment on the sediment control building in the Harapan River, Jayapura district. This research uses BWS Papua data, the data obtained is rainfall data and topographic data. Research stages include literature study, secondary data collection of sediment data obtained from BWS Papua. The results of this research show that the erosion rate using the USLE method on the Harapan River is 2.51 tons/ha/year and the sedimentation rate using the USLE method is 13.15 tons/year, with the sediment rate obtained being 13.15 tons/year associated with the storage volume in the sediment control building of 13093.52 m3 which is considered still capable of holding the sediment that occurs in the Harapan River, Jayapura Regency.